Intra-species diversity of Clostridium perfringens: A diverse genetic repertoire reveals its pathogenic potential - Camargo, Anny; Guerrero-Araya, Enzo; Castañeda, Sergio; Vega, Laura; Cardenas-Alvarez, María X.; Rodríguez, César; Paredes-Sabja, Daniel; Ramírez, Juan David; Muñoz, Marina (Frontiers in Microbiology, 2022)
Clostridium perfringens is the causative agent of many enterotoxic diseases in humans and animals, and it is present in diverse environments (soil, food, sewage, and water). Multilocus Sequence Typing (MLST) and Whole Genome Sequencing (WGS) have provided a general approach about genetic diversity of C. perfringens, however, those studies are limited to specific locations and often include a reduced number of genomes. In this study, 372 C. perfringens genomes from multiple locations and sources were used to assess the genetic diversity and phylogenetic relatedness of this pathogen. In silico MLST was used for typing the isolates and the resulting sequence types (STs) were assigned to clonal complexes (CC) based on allelic profiles that differ from its founder by up to double-locus variants (DLVs). A pangenome analysis was conducted and a core genome-based phylogenetic tree was created to define phylogenetic groups. Additionally, key virulence factors, toxinotypes, and antibiotic resistance genes were identified using ABRicate against Virulence Factor Database (VFDB), TOXiper and Resfinder, respectly. The majority of the C. perfringens genomes found in publicly available databases were derived from food (n=85) and bird (n=85) isolates. A total of 195 STs, some of them shared between sources such as food and human, horses and dogs, and environment and birds, were grouped in 25 CCs and distributed along five phylogenetic groups. Fifty-three percent of the genomes were allocated to toxinotype A, followed by F (32%), and G (7%). The most frequently found virulence factors based on >70% coverage and 99.95% identity were plc (100%), nanH (99%), ccp (99%), and colA (98%), which encode an alpha-toxin, a sialidase, an alpha-clostripain, and a collagenase respectively, while tetA (39.5%) and tetB (36.2%), which mediate tetracycline resistance determinants, were the most common antibiotic resistance genes detected. The analyses conducted showed a better view about the possible spread of this pathogen among hosts, either by direct contact or by contaminated food. Our results confirm a great diversity of C. perfringens with a large number of virulence factors that vary among phylogroups and antibiotic resistance markers, especially to tetracyclines, aminoglycosides, and macrolides, which highlight its importance as an emerging pathogen.